ULTRASONIC CLEANING PROCESS CONTROL SYSTEM - SELIUK, DANIL; SHEVCHENKO, VADYM (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Ultrasonic cleaning provides the opportunity to effectively clean parts in various manufacturing processes. Compared to other cleaning methods, it has several advantages, including high quality surface finishes, less toxic cleaning agents, and significant reduction in manual labor. The work developed an automated system to ensure the ultrasonic processing of parts. The literature review was conducted regarding the parameters that affect the process and the achievements in this field were analyzed. The system is implemented on the ESP-32 microcontroller. Two controlled parameters – transparency and conductivity of the solution – were used to analyze the completion of the cleaning process. The cleaning process was considered complete when these parameters stopped changing. The authors carried out the hardware implementation of the developed system and developed its operation algorithm. At the beginning of the process, the system checks the bath for the presence of liquid. If it is absent, the conductivity sensor will show infinite resistance. The system then waits for 60 seconds and starts the processing. If the transparency of the liquid changes, the system starts a counter, the value of which changes when the conductivity changes by a set step. If the counter stops changing, the process stops. The cleaning is considered complete. This method is applicable for both plastic and metal parts. The research results showed that the presence of soapy solution significantly changes the cleaning time compared to water, almost by 50%. However, the change in temperature in the soapy solution leads to a change in speed by only 10%. The temperature change when using plain water significantly affects the processing time and reduces it by 30%. The analysis of the results showed reliable and accurate operation of the system during the cleaning process. In the future, it is planned to improve the control system by adding new measurement values to provide more efficient optimization of the parts cleaning process.
Keywords: ultrasonic; cleaning; automated system; cavitation; algorithm